Danhe granule ameliorates nonalcoholic steatohepatitis and fibrosis in rats by inhibiting ceramide de novo synthesis related to CerS6 and CerK. (15th September 2022) - Zhu, Meixia; Jia, Zhixin; Yan, Xiaoning; Liu, Lirong; Fang, Cong; Feng, Menghan; Dai, Yihang; Zhang, Yinhuan; Wu, Hao; Huang, Beibei; Li, Yueting; Liu, Jie; et al.
Abstract: Ethnopharmacological relevance: Danhe granule (DHG) is used by Chinese doctors to treat blood stasis, phlegm and dampness. Its lipid-lowering ability has been investigated in our previous research. However, the anti-liver inflammatory and fibrotic effects and mechanism of action of DHG in non-alcoholic steatohepatitis (NASH) have not been explored. Aim of the study: To evaluate the ameliorative effects of DHG on liver inflammation and fibrosis in a methionine/choline-deficient (MCD) diet-induced NASH rat model, and its underlying mechanism. Materials and methods: Sprague-Dawley rats were fed an MCD diet for two weeks and then treated with or without DHG by oral gavage for eight weeks. Their body weight and liver index were measured. The serum alanine aminotransferase (ALT) and aspartate transaminase (AST) activities as well as the liver triglyceride (TG) and free fatty acid (FFA) levels were tested using reagent kits. Inflammatory cytokines, including Tnf-α, Il-β and Il-6, and fibrosis genes, including Acta2, Col1a1, Col1a2 and Tgf-β were examined by real-time quantitative PCR (RT-qPCR). Hematoxylin-eosin (H&E), Oil Red O, Masson's and Sirius Red staining were used to observe liver changes. The plasma and liver ceramide levels were analyzed using HPLC-QQQ-MS/MS. The expression of serine palmitoyl-CoA transferase ( Spt ), ceramide synthase 6 ( Cers6 ), dihydroceramide desaturase 1 ( Des1 ), glucosylceramide synthase ( Gcs ), and ceramide kinase ( Cerk ) mRNA was assayed by RT-qPCR, while the protein expression of CerS6, DES1, GCS, CerK, and casein kinase 2α (CK2α) was tested by western blotting (WB). CerS6 degradation was evaluated using a cycloheximide (CHX) assay in vitro . Results: The liver index decreased by 20% in DHG groups and the serum ALT and AST decreased by approximately 50% and 30%, respectively in the DHG-H group. The liver Oil Red O staining, TG, and FFA changes showed that DHG reduced hepatic lipid accumulation by approximately 30% in NASH rats. H&E, Masson's and Sirius Red staining and the mRNA levels of Tnf-α, Il-β, Il-6, Acta2, Col1a1, Col1a2 and Tgf-β revealed that DHG alleviated liver inflammation and fibrosis in NASH rats. The ceramide (Cer 16:0), and hexosylceramide (HexCer 16:0, HexCer 18:0, HexCer 22:0, HexCer 24:0 and HexCer 24:1) levels decreased by approximately 17–56% in the plasma of the DHG-M and H rats. The Cer 16:0 content in the liver decreased by 20%, 50%, and 70% with the DHG-L, M, and H treatments; additionally, the dhCer 16:0, Cer 18:0, HexCer 18:0, HexCer 20:0 Cer 22:0–1P, Cer 24:0–1p, Cer 24:1–1p, and Cer 26:1–1p levels decreased in the DHG groups. The mRNA and protein expression levels of DES1, GCS, Cerk, CerS6, and CHX assay indicated that DHG decreased the mRNA and protein expression levels of CerK and reduced CerS6 protein expression by promoting its degradation. Additionally, DHG attenuated the protein expression of CK2α which could increase CerS6 enzymatic activity by phosphorylating its C-terminal region. Conclusion: DHG ameliorated the levels of liver FFA and TG and inflammation and fibrosis in MCD-induced rats, which were associated with decreasing ceramide species in the plasma and liver by reducing the expression levels of CerS6 and CerK. Graphical abstract: Image 1 Highlights: DHG ameliorated liver lipid accumulation, inflammation and fibrosis induced by an MCD diet in rats. DHG decreased Cer 16:0 and HexCer 16:0 in plasma and Cer 16:0, dhCer 16:0, HexCer 18:0 and Cer 22:0–1P in liver by HPLC-QQQ-MS/MS detection. DHG decreased the mRNA and protein expression levels of CerK and CerS6 by promoting its degradation and reducing CK2α protein expression to decrease CerS6 activity.